A Review of the Applications of Nanofluids and Related Hybrid Variants in Flat Tube Car Radiators - Abbasi, Amirmohammad; Gharsi, Sogol; Dinarvand, Saeed (Fluid dynamics & materials processing, 2025)
The present review explores the promising role of nanofluids and related hybrid variants in enhancing the efficiency of flat tube car radiators. As vehicles become more advanced and demand better thermal performance, traditional coolants are starting to fall short. Nanofluids, which involve tiny nanoparticles dispersed into standard cooling liquids, offer a new solution by significantly improving heat transfer capabilities. The article categorizes the different types of nanofluids (ranging from those based on metals and metal oxides to carbon materials and hybrid combinations) and examines their effects on the improvement of radiator performance. General consensus exists in the literature that nanofluids can support better heat dissipation and enable accordingly the development of smaller and lighter radiators, which require less coolant and allow more compact vehicle designs. However, this review demonstrates that the use of nanofluids does not come without challenges. These include the long-term stability of these fluids and material compatibility issues. A critical discussion is therefore elaborated about the gaps to be filled and the steps to be undertaken to promote and standardize the use of these fluids in the industry.